Newborn screening programmes in Europe: arguments and efforts regarding harmonization : Part 2 - From screening laboratory results to treatment, follow-up and quality assurance - Burgard, Peter; Rupp, Kathrin; Lindner, Martin; Haege, Gisela; Hoffmann, Georg F. (Journal of inherited metabolic disease, 2012)
In a survey conducted in 2010/2011 data from the 28 EU member states, four EU candidate states (Croatia, FYROM, Iceland, Turkey), three potential EU candidate states (Bosnia Herzegovina, Montenegro, Serbia), and two EFTA states (Norway and Switzerland) were collected. The status and function of newborn screening (NBS) programmes were investigated from the information to prospective parents and the public via confirmation of a positive screening result up to decisions on treatment. This article summarises the results from screening laboratory findings to start of treatment. In addition we asked about the existence of feedback loops reporting the conclusions of confirmation of screening results to the screening laboratory and communication of long-term outcome to diagnostic units and possibly existing central registries. Parallel to the description of actual practices of where, how and by whom the different steps of the programmes are executed, we also asked for the existence of guidelines or directives regulating the screening programmes, material to support information of parents about diagnoses and treatment and training facilities for professionals involved in the programmes. This survey gives a first comprehensive overview of the steps following a positive screening result in European NBS programmes. The 37 data sets reveal substantial variation of national screening panels, but also a lot of similarities. Analysis across all countries revealed that actual practice is often organised but not regulated by guidelines. Material to inform patients is available more often for explaining treatment (69 %) than explaining the necessity of confirmatory diagnostics (41 %). Training of professionals is rarely regulated by a guideline (2 %), but is offered for paediatricians (40 %) and dieticians (29 %) and only rarely for other professions (e.g. geneticists, clinical nurse specialists, psychologists). Registry-based evaluation of long-term outcome is as yet almost nonexistent (3 %).
First Online: 28 April 2012
Gesehen am 08.06.2018